SIFAT PAPAN WOL KAYU DARI POHON TUSAM DISADAP DAN TIDAK DISADAP - I Sulastiningsih M Sulastiningsih; Rozak Memed; Paribroto Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The results of a study on the properties of wood-wool board made from tapped and untapped pine (Pinus merkusii Jungh et de Vriese) is reported in this paper. The wood is obtained from West Java.The result shows that hydration temperature of tapped tree is 36oC, and untapped pine is 43°C. Based on this data, wood from tapped pine tree can be classified as medium and that from untapped pine as good for wood-wool board material. In general the wood-wool board properties of both wood sources meet DIN standard. The effect of tapping, cement proportion, kind of catalyst, and interaction between cement proportion and kind of catalyst on the mechanical properties of wood-wool board are significant. Tapped pine is better than untapped pine as raw material for wood-wool board.